A Review Paper on Solar Tree Mechanism and Installation for Energy Generation - Radhika Pandey; Poonam Yadav (Journal of Power Electronics and Devices, 2020)
Nowadays solar energy is the most explored and attainable area of but exploration is not so easy and solar energy is accepted as a key resource for the future of the world. Solar energy can be utilized to cover energy demand over a significant part of the countries. The solar tree is the most popular example of utilized solar energy. Solar Energy is free, inexhaustible, and nonpolluting This paper represents the reviews about the development of Solar Tree for domestic application and the solar tree considering the average requirement of a small Indian house. A solar tree is the most economical way of exploiting solar energy. It can make use of the energy occupying less space.